2020
DOI: 10.1001/jamacardio.2020.0246
|View full text |Cite
|
Sign up to set email alerts
|

Association of FADS1/2 Locus Variants and Polyunsaturated Fatty Acids With Aortic Stenosis

Abstract: IMPORTANCE Aortic stenosis (AS) has no approved medical treatment. Identifying etiological pathways for AS could identify pharmacological targets. OBJECTIVE To identify novel genetic loci and pathways associated with AS. DESIGN, SETTING, AND PARTICIPANTS This genome-wide association study used a case-control design to evaluate 44 703 participants (3469 cases of AS) of self-reported European ancestry from the Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort (from January 1, 1996, to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…Since this variant genotype has been shown to alter both omega-3 and omega-6 PUFA metabolism and to lower AA generation from linoleic acid ( Sasaki et al, 2019 ; Chen et al, 2020 ), those findings provide a potential link between PUFA and AVS. This is further reinforced by the finding that higher systemic levels of AA furthermore are associated with aortic valve calcification ( Chen et al, 2020 ). However, the local valve levels rather than systemic levels of PUFA may be decisive for their availabilities as substrates for the biosynthesis of lipid mediators.…”
Section: Omega-3 Pufas In Avsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since this variant genotype has been shown to alter both omega-3 and omega-6 PUFA metabolism and to lower AA generation from linoleic acid ( Sasaki et al, 2019 ; Chen et al, 2020 ), those findings provide a potential link between PUFA and AVS. This is further reinforced by the finding that higher systemic levels of AA furthermore are associated with aortic valve calcification ( Chen et al, 2020 ). However, the local valve levels rather than systemic levels of PUFA may be decisive for their availabilities as substrates for the biosynthesis of lipid mediators.…”
Section: Omega-3 Pufas In Avsmentioning
confidence: 97%
“…Genome-wide association and Mendelian randomization studies have identified a genetic variant in the FADS1/2 loci associated with AVS ( Yuan et al, 2019 ), where each copy of the minor-C allele reduced more than 10% the odds of the disease ( Chen et al, 2020 ). Since this variant genotype has been shown to alter both omega-3 and omega-6 PUFA metabolism and to lower AA generation from linoleic acid ( Sasaki et al, 2019 ; Chen et al, 2020 ), those findings provide a potential link between PUFA and AVS. This is further reinforced by the finding that higher systemic levels of AA furthermore are associated with aortic valve calcification ( Chen et al, 2020 ).…”
Section: Omega-3 Pufas In Avsmentioning
confidence: 99%
“…To our knowledge, associations of PUFAs in phospholipids extracted from plasma and AVS specifically only come from one genome wide association studies (GWAS) study [10]. In pooled results from two previous studies, LA and ALA were inversely associated with aortic valve calcium (AVC), a predecessor of AVS.…”
Section: Circulating Pufas As Biomarkersmentioning
confidence: 99%
“…The importance of the latter as causal factor for AVS is illustrated by results from Mendelian Randomization (MR), in which body mass and fat mass indexes exhibit stronger associations with AVS compared with other cardiovascular diseases [8]. The genetic variants located in proximity to LPA and FADS1 have genome-wide association with AVS [9,10] and coronary artery disease [11] and acting through affecting levels of lipoprotein (a) (Lp(a)) and fatty acids, respectively. Interestingly, MR studies have shown a stronger association of these genetically determined risk factors with AVS compared with other cardiovascular diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…IHD and AF have been reported to have more than 100 disease susceptibility loci as already described (2,3), where IHD has been suggested to be strongly associated with lipids, hypertension, diabetes, inflammation, and other atherosclerosis-related traits, while AF has been suggested to have mechanisms strongly related to HF, such as cardiac development and myocardial contractility, apart from electrophysiological traits. As for valvular disease, Chen et al (20) have recently identified nine disease-susceptibility loci in aortic stenosis, suggesting the involvement of lipids and the immune system. In addition, there are a few reports on mitral valve prolapse syndrome (21,22) in which mitral valve repair and cardiac development are reported to be involved in the pathogenesis.…”
Section: Genetic Analysis For Diseases Leading To Hfmentioning
confidence: 99%